Kaputol ng isang awit (Quezon City Viva Films, 1999)
Sarah has everything ordinary women could only wish for, beauty, wealth, fame. She's the country's most popular performer, everyone admire and even envies her. Yet inspite of all she has, Sarah is not happy. There remains a dark void in her life as she continue to look and yearn for that one person who all her life has been missing, her father.
VCD
Sharon Cuneta, Gary Valenciano, Tonton Gutierrez
Keywords: Family; Drama; Feature films